Resistance test of rice (Oryza sativa) varieties by Paraeucosmetus pallicornis Dallas. (Hemiptera: Lygaedae) in the screen house - cici khairi gusnarsih; cyccu - tobing; mukhtar iskandar pinem (Universitas Sumatera Utara, 2019)
The research was aimed to determine the resistance of rice plant varieties against Paraeucosmetus pallicornis in screen house. This research was conducted in the screen house of Universitas Sumatera Utara from July until November 2017 using factorial randomized block design (RBD) with two factors and four replications. The first factor was the time of introduction (4, 6, 8, 10 weeks after planting) and the second factor was rice varieties (Ciherang, Inpari 32, Mekongga, dan Mapan P-05). The results showed that all of varieties was classified as scale 1 (resistant) against P. pallicornis. The highest ratio the intensity of attack tested based on time introduction was 10, 4 , 8, and 6 wap respectively. Key words : Paraeucosmetus pallicornis, rice, plant resistance, variety